E-Commerce Solusi Jitu Masalah Perekonomian - Mirza Noer Rahman; Rayyan Firdaus (Journal of Islamic Economics and Finance, 2024)
Electronic-Commerce (e-commerce) or electronic commerce is a way to sell and buying goods and services via the internet network Electronic-Commerce (e-commerce) or electronic commerce is a way to sell and purchase goods and services via the internet network. When a customer finds a product they want to purchase, they can add it to their shopping cart and check out using their debit or credit card. Some payment processors even allow to accept payments via cryptocurrency and other alternative payment methods